Episode 2: All walks of life: from hate to healing - Chaudhry, Irfan; Bukhari, Iman (My University, 2019)
Alberta is located on Treaty land. An acknowledgment of the historical legacy of hateful treatment towards the Indigenous community in Canada culminated with the federal government’s Truth and Reconciliation Calls to Action in 2015. In this episode, we outline what, if anything, has changed in Alberta and how Indigenous knowledge can help us heal from historical and current narratives of hate. Hosted by Irfan Chaudry and Iman Bukhari.
Keywords: indigenous peoples; hate; Alberta